Shadows and observational appearance of a new family of Ayón-Beato-García black holes. (1st December 2022) - Mou, Ping-Hui; Chen, Yun-Xian; He, Ke-Jian; Li, Guo-Ping
Abstract: In this paper, we study the shadows and observational appearance of the Ayón-Beato-García (ABG) black hole, which is surrounded by a thin disk accretion. For a four-dimensional ABG black hole, as the charge q increases, the event horizon r +, radius r p and impact parameter b p of the photon sphere decrease, while the maximum value of effective potential V eff increases. However, as the term γ associated with nonlinear electrodynamics increases, the related physical quantities r +, r p and b p increase, but the maximum value of V eff decreases. When the light ray reaches the vicinity of the ABG black hole, one can observe the trajectories of the light rays appearing as three types, i.e., direct emission, lens ring and photon ring. Furthermore, the shadows and the observational appearance of the ABG black hole are studied. The results show that the charge q and the term γ have a great influence on the shape and intensity of the black hole shadow. When the relevant state parameters change or the emission model changes, it can be argued that it is the direct emission that plays a decisive role in the total observed intensity of the ABG black hole, while the contribution of the lens ring to the total observed intensity is small and the photon ring makes almost no contribution.